Boolean Algebra – How to Reduce Boolean Algebra Expressions

boolean-algebralogic

Presented with the Boolean function $F$, I must reduce this to its most simple form. I know the answer is $(A+BD)$, but I am lost on how to get there.

$F=((((A'B)'+D')'+A)(((A'B)'+D')'+C'))+((D'+D)(C'C)) + AC$

Best Answer

$ XX' = 0$
$X+X' = 1$
$(X+Y)' = X'Y'$.
$(XY)' = X'+Y'$
$(X+Y)(X+Z) = X+YZ$

If you use these, the expression reduces to,

$A'BD+AC'+AC = A'BD+A(C+C') = A+A'BD$

Now,

$X+X'Y = X+Y$

The expression thus becomes, $A+A'BD = A+BD$

Related Question